Impaired Activation of Visual Attention Network for Motion Salience Is Accompanied by Reduced Functional Connectivity between Frontal Eye Fields and Visual Cortex in Strabismic Amblyopia - Wang, Hao; Crewther, Sheila G.; Liang, Minglong; Laycock, Robin; Yu, Tao; Alexander, Bonnie; Crewther, David P.; Wang, Jian; Yin, Zhengqin (Frontiers in Human Neuroscience, 2017)
Strabismic amblyopia is now acknowledged to be more than a simple loss of acuity and to involve alterations in visually driven attention, though whether this applies to both stimulus-driven and goal-directed attention has not been explored. Hence we investigated monocular threshold performance during a motion salience-driven attention task involving detection of a coherent dot motion target in one of four quadrants in adult controls and those with strabismic amblyopia. Psychophysical motion thresholds were impaired for the strabismic amblyopic eye, requiring longer inspection time and consequently slower maximum target speed for detection compared to the fellow eye or control eyes. We compared fMRI activation and functional connectivity between four ROIs of the occipital-parieto-frontal visual attention network (primary visual cortex [V1], motion sensitive area V5, intraparietal sulcus [IPS] and frontal eye fields [FEF]), during a suprathreshold version of the motion-driven attention task, and also a simple goal-directed task, requiring voluntary saccades to targets randomly appearing along a horizontal line. Activation was compared when viewed monocularly by controls and the amblyopic and its fellow eye in strabismics. BOLD activation was weaker in IPS, FEF and V5 for both tasks when viewing through the amblyopic eye compared to viewing through the fellow eye or control participants’ non-dominant eye. No difference in V1 activation was seen between the amblyopic and fellow eye, nor between the two eyes of control participants during the motion salience task, though V1 activation was significantly less through the amblyopic eye than through the fellow eye and control group non-dominant eye viewing during the voluntary saccade task. Functional correlations of ROIs within the attention network were impaired through the amblyopic eye during the motion salience task, whereas this was not the case during the voluntary saccade task. Specifically, FEF showed reduced functional connectivity with visual cortical nodes during the motion salience task through the amblyopic eye, despite suprathreshold detection performance. This suggests that the reduced ability of the amblyopic eye to activate the frontal components of the attention networks may help explain the aberrant control of visual attention and eye movements in amblyopes.